Morfopatologia y aislamientos microbiologicas en cerdos neumonicos - Bulnes, C.A.=700 1 Joa, R.; Martinez, A.
(Es, En)
Ilus., 17 ref.
Keywords: CERDO; INFECCION; NEUMONIA; PATOLOGIA; ANATOMIA ANIMAL; CUBA